Tradisi Selamatan Ketupat dan Serabi Sebagai Tolak Bala di Masa Pandemi Covid-19 Pada Masyarakat Desa Sidorenggo, Kecamatan Ampelgading Kabupaten Malang - Rike Widya Lestari; Siti Awaliyah; Abd. Mu’id Aris Shofa (FKIP, Universitas Palangka Raya, 2022)
This article aims to discuss the reasons for the community to carry out the Ketupat and Serabi Salvation during the Covid-19 pandemic, the process of implementing the Ketupat and Serabi Salvation, and public opinion about the implementation of the Ketupat and Serabi Salvation. The research method used is qualitative with a descriptive approach. The reason people carry out the Ketupat and Serabi Salvation during the Covid-19 pandemic because there are many victims who died because of this outbreak. The process of implementing the Ketupat and Serabi Salvation is make seven pieces of Ketupat and Serabi then pray individually or together in the prayer room or mosque. Ketupat and serabi that have been prayed for are consumed by all family members so that they are given safety and health by God. The implementation of the Ketupat and Serabi Salvation in Sidorenggo Village, Ampelgading District, Malang Regency during the Covid-19 pandemic is a form of public trust in a tradition of Ketupat and Serabi salvation that has been carried out for generations during a deadly disease outbreak